Academic visit to Fibertex Personal Care Sdn. Bhd.: bridging theory and industry practice / Nurulnadiah Zulkhaire ... [et al.] - Zulkhaire, Nurulnadiah; Anuar, Aliah Farzana; Mohd Aziz, Nur Ilya Syamimi; Musa, Atiyyah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
On Thursday, May 16, 2024, all second-semester students of the Diploma in Textile and Clothing Technology programme (AS122) at UiTM Cawangan Negeri Sembilan, Kampus Kuala Pilah, had the privilege to go on an academic visit to Fibertex Personal Care Sdn. Bhd. in Nilai, Negeri Sembilan. Fibertex, a leading global manufacturer, produces nonwoven fabrics for essential items such as baby nappies, sanitary pads, and adult incontinence products. Spanning from 9:00 a.m. to 12:00 p.m., this academic visit was organised to enhance the learning experience and to give a firsthand insight into the production of nonwoven fabrics, particularly for personal care uses. It also allowed us to observe industrial machinery and processes in action and interact with industry professionals. This was an exciting opportunity for all of us to connect with what we had been learning in class to real-world practices while sparking interest in potential career opportunities in the textile and manufacturing sectors.